Reduced Diversity and Imbalance of Fecal Microbiota in Patients with Ulcerative Colitis - Nemoto, Hideyuki; Kataoka, Keiko; Ishikawa, Hideki; Ikata, Kazue; Arimochi, Hideki; Iwasaki, Teruaki; Ohnishi, Yoshinari; Kuwahara, Tomomi; Yasutomo, Koji (Digestive diseases and sciences, 2012)
Background Clinical observations and experimental colitis models have indicated the importance of intestinal bacteria in the etiology of ulcerative colitis (UC), but a causative bacterial agent has not been identified. Aim To determine how intestinal bacteria are associated with UC, fecal microbiota and other components were compared for UC patients and healthy adults. Methods Fresh feces were collected from 48 UC patients. Fecal microbiota were analyzed by use of terminal-restriction fragment length polymorphism (T-RFLP), real-time PCR, and culture. The concentrations of organic acids, indole, and ammonia, and pH and moisture, which are indicators of the intestinal environment, were measured and compared with healthy control data. Results T-RFLP data divided the UC patients into four clusters; one cluster was obtained for healthy subjects. The diversity of fecal microbiota was significantly lower in UC patients. There were significantly fewer Bacteroides and Clostridium subcluster XIVab, and the amount of Enterococcus was higher in UC patients than in healthy subjects. The fecal concentration of organic acids was significantly lower in UC patients who were in remission. Conclusion UC patients have imbalances in the intestinal environment—less diversity of fecal microbiota, lower levels of major anaerobic bacteria ( Bacteroides and Clostridium subcluster XIVab), and a lower concentration of organic acids.